2020
DOI: 10.1371/journal.pone.0241344
|View full text |Cite
|
Sign up to set email alerts
|

Using judgment bias test in pet and shelter dogs (Canis familiaris): Methodological and statistical caveats

Abstract: It is now widely agreed that a positive affective state is a crucial component of animal well-being. The judgment bias test represents a widespread tool used to assess animals’ optimistic/pessimistic attitude and to evaluate their emotional state and welfare. Judgment bias tests have been used several times with dogs ( Canis familiaris ), in most cases using a spatial test with a bowl placed in ambiguous positions located between a relatively positive trained location (P) which contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The present results also indicate that previous studies conducted on dogs without their owners present may not have reflected the dogs' true abilities to follow human cues, as suggested by Burani, Barnard, Wells, Pelosi, and Valsecchi [40]. Our results also support the findings of previous studies that have found that dogs largely react better to their owners than a stranger [17,41].…”
Section: Discussionsupporting
confidence: 88%
“…The present results also indicate that previous studies conducted on dogs without their owners present may not have reflected the dogs' true abilities to follow human cues, as suggested by Burani, Barnard, Wells, Pelosi, and Valsecchi [40]. Our results also support the findings of previous studies that have found that dogs largely react better to their owners than a stranger [17,41].…”
Section: Discussionsupporting
confidence: 88%
“…Training could also act as cognitive enrichment, influencing the animal's affective state and altering test performance (Roelofs et al, 2016). Furthermore, in dogs, researchers are usually present during the test, potentially influencing the dog's judgement bias (Burani et al, 2020). How can cognitive bias researchers overcome these challenges?…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive bias research in dogs has focused on judgement bias, rather than attention bias (Barnard et al, 2018;Burani et al, 2020;Burman et al, 2011;Duranton and Horowitz, 2019;Mendl et al, 2010). To our knowledge, only one study has used attention bias to assess dog welfare.…”
Section: Introductionmentioning
confidence: 99%
“…In the test phase, the dog is presented with ambiguous stimuli over a series of trials, in this case, a bowl in one of three positions between the far right ‘Positive’ and far-left ‘Negative’ positions; either ‘Near Negative’ (NN), ‘Middle’ (M) or ‘Near Positive’ (NP). The dog’s latency to approach these ambiguous stimuli has been widely used as a measure of that dog’s affective state (e.g., Burani et al 2020 ; Burman et al 2011 ; Gruen et al 2019 ; Karagiannis et al 2015 ; Mendl et al 2010 ; Müller et al 2012 ; Wells et al 2017 and Willen et al 2019 who used the five bowl protocol as described above, and Duranton and Horowitz 2019 ; Kis et al 2015 and Harvey et al 2020 who used a modified protocol with M as the only ambiguous location). If the dog is faster to approach the ambiguous bowl, it indicates a positive judgement bias (more “optimistic”), whereas a slower approach suggests a negative judgement bias (more “pessimistic”).…”
Section: Introductionmentioning
confidence: 99%
“…This may be seen by the dog approaching the bowls with greater latencies (more slowly), or not approaching at all. Within the canine literature, Burani et al ( 2020 ) tested for affect differences between shelter and pet dog populations, and found a learning effect within a single testing session for the ambiguous Middle position on the second presentation, and for the Near Negative position on the third presentation (approaches to the Near Positive location were non-significantly different). These results indicate that dogs may have been learning within one testing session that the ambiguous bowls were not rewarded.…”
Section: Introductionmentioning
confidence: 99%